STRUCTURAL ANALYSIS OF A LIGHTWEIGHT ELECTRIC VEHICLE CHASSIS: Received: 08th April 2024 Revised: 17th May 2024, 21st May 2024, 23rd May 2024 Accepted: 01st May 2024 - Babs, V. Omidiji,; Ayodele, A. Daniyan,; Hakeem, A. Owolabi,,; Kunle, M. Oluwasegun,; Daniel, Egbebunmi,; Olusegun, E. Fabunmi, (MATTER: International Journal of Science and Technology, 2024)
This study presents a comprehensive investigation into the design and structural analysis of lightweight chassis for electric vehicles. A chassis needs to be able to withstand twist, shock, vibration, and other stresses caused by acceleration, braking, road condition, and shock initiated by other parts of a vehicle. It should carry a maximum load under all operating conditions. Two materials, 304L steel, and Ti-6AL-4V alloy were evaluated, with parameters such as total deformation, equivalent stress, and equivalent elastic strain under consideration. The outcome of the Finite Element Analysis revealed that Ti-6AL-4V can withstand higher stresses than 304L Steel. By investigating the static behaviors of the chassis under static loading due to weight and overload conditions, Ti-6AL-4V was chosen as a suitable replacement for a 304L Steel chassis.